Social Innovation and Social Policy – Promises and Risks. Issue 3 (3rd April 2014) - Sinclair, Stephen; Baglioni, Simone
<x content-type="archive" xml:space="preserve">Abstract</x> Social innovation (SI) is an increasingly prominent but contested issue in discussions of social policy reform. Although not yet a familiar concept, nor widely understood (least of all by policy makers), it has entered mainstream policy discourses. However whether SI marks a significant departure in either theory or in practice, or merely in rhetoric, remains to be determined. This Review Article, and the Themed Section as a whole, aims to set out some of the questions social policy analysts should ask about SI, and to help clarify whether or not it is a significant development which merits attention. The Review begins by considering some of the reasons for the recent interest shown in SI before clarifying the meaning of the concept and outlining some of the different forms SI has taken. This discussion is followed by a consideration of some of the practical and theoretical questions which SI raises for social policy analysis. The Review concludes that social policy analysts cannot afford to ignore SI, but that the most effective contribution the discipline can make is to apply a critical empirical perspective to test the significance, value and impact of SI.